The Catholic Church and Consolidation of Democratic Civil Society in Spain - Requena-Santos, Félix (Taylor & Francis Online, 2019)
This article examines how the Catholic Church assisted the transition to democracy and consolidation of democratic civil society in Spain through a position of political neutrality. By abstaining from any active role in political parties, abandoning pretence of moral monopoly and embracing pluralism, it helped facilitate the establishment of civil society. Analytically, the path dependence mechanism, Huntington’s theory of democratisation and the secularisation of religion theory are used to explain the how the Spanish Catholic Church helped establish the bases of civil society in democratic Spain.
Keywords: España - Iglesia Católica; España - Historia - 1975-1982 (Transición); Sociedad civil; Catholic Church; Spain; Civic networks; Democratic process; Democratic transition; Civil society